Project based Learning Integrated with CAD Software to Improve Technical Drawing Skills - Fauzansyah, Tengku Ahmad; Edyan, Roly; Hakiki, Muhammad (Juwara: Jurnal Wawasan dan Aksara, 2025)
This study investigates the impact of Project Based Learning (PBL) integrated with Computer Aided Design (CAD) software on improving technical drawing skills among vocational high school students. The experimental design involved two groups: an experimental group that received PBL based instruction using CAD software, and a control group that followed traditional instructional methods. The results revealed a significant improvement in the technical drawing skills of the experimental group, as indicated by higher post-test scores compared to the control group. These findings suggest that PBL, when coupled with CAD tools, fosters active learning, critical thinking, and enhances students' ability to visualize and create accurate technical drawings. Additionally, the project-based approach promoted collaboration, real world problem solving, and digital literacy, key competencies in vocational education. The study also identified a substantial effect size (Cohens d=2.97), emphasizing the significant educational impact of the PBL CAD integration. Despite the promising results, the study highlights limitations in terms of generalizability due to the single school sample and suggests further exploration of affective and behavioral outcomes in future research. In conclusion, the integration of PBL and CAD software represents an effective pedagogical strategy for improving technical drawing skills and preparing students for the demands of the modern workforce.